2020
DOI: 10.3390/insects11080457
|View full text |Cite
|
Sign up to set email alerts
|

EPNs Exhibit Repulsion to Prenol in Pluronic Gel Assays

Abstract: Entomopathogenic nematodes (EPNs) are lethal parasites of insects that have become valuable in biological control and as a model system for studying host–parasite interactions, behavioral ecology, neurobiology, and genomics, among other fields. Their ability to locate hosts is paramount to successful infection and host seeking has been extensively studied in many species in the lab. Here, we explored the usefulness of pluronic gel as a medium to assess EPN host seeking in the lab by characterizing the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The ammonia present in insect feces can inhibit EPN IJ responses to hosts ( Grewal et al, 1993 ) and may trigger IJ emergence ( San-Blas et al, 2008 ). Additionally, compounds such as prenol (3-methyl-2-buten-1-ol) appear to alter EPN behavior; recent assessments ( Kin et al, 2019 and Baiocchi et al, 2020 ) observed that while all of the EPN species tested were repelled by prenol, only a subset of the species tested responded to prenol exposure by increasing rates of dispersal ( Kin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ammonia present in insect feces can inhibit EPN IJ responses to hosts ( Grewal et al, 1993 ) and may trigger IJ emergence ( San-Blas et al, 2008 ). Additionally, compounds such as prenol (3-methyl-2-buten-1-ol) appear to alter EPN behavior; recent assessments ( Kin et al, 2019 and Baiocchi et al, 2020 ) observed that while all of the EPN species tested were repelled by prenol, only a subset of the species tested responded to prenol exposure by increasing rates of dispersal ( Kin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…When hydrogels have been used to examine nematode behaviors in three dimensions, they have maintained the traditional approaches of using large-format dishes or wells (Baiocchi et al, 2020;Guisnet et al, 2021;Lesanpezeshki et al, 2019). We combined advances in microdevice fabrication and hydrogel utilization for nematode culture to design a 96-well device that allows nematodes to freely burrow through a three-dimensional environment toward a cue or away from a repellent.…”
Section: Elegans Gustatory Behaviormentioning
confidence: 99%
“…Recently, three-dimensional hydrogel-based nematode burrowing assays have been developed, and it has been shown that rearing nematodes in a three-dimensional environment reveals natural behaviors that are masked when using two-dimensional arenas (Baiocchi et al, 2020;Guisnet et al, 2021). Additionally, microfluidic devices have been designed to probe nematode sensory behaviors in an aqueous environment, increasing quantitative sensitivity (Chronis et al, 2007;Hu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%